E-learning spaces and the digital university. Issue 3 (6th June 2016) - Pates, Dominic; Sumner, Neal
Abstract : Purpose: – The purpose of this paper is to share lessons already learned and work currently in progress from one higher education institution's experiences of developing several flexible and technology-enhanced active learning spaces. It further proposes that the potential of such spaces can be more fully realised through the enactment of programmes of digital literacy development amongst their users. Design/methodology/approach: – In identifying a convergence of profound challenges facing higher education and proposing that innovations in physical learning spaces are one approach to addressing such challenges, the paper examines a number of institutional policies and initiatives for rethinking and redesigning several physical classroom environments. It sets internal findings and position statements amidst a broader context of relevant field literature. Findings: – The paper provides insights from several years of experience in higher education learning space development, including the benefits of iterative experimentation, the consultative role of a multi-stakeholder specialist group, the challenges of balancing pedagogic need with often conflicting institutional requirements and the value of varied programmes of staff development. Originality/value: – This paper's insights will be of value to individuals and institutions engaged in reconsidering their provision of physical classroom spaces in higher education and to those promoting the effective use of learning spaces in the digital university.